Identification of a Novel, Recurrent SLC44A1‐PRKCA Fusion in Papillary Glioneuronal Tumor. (23rd July 2012) - Bridge, Julia A.; Liu, Xiao‐qiong; Sumegi, Janos; Nelson, Marilu; Reyes, Christine; Bruch, Leslie A.; Rosenblum, Marc; Puccioni, Mark J.; Bowdino, Bradley S.; McComb, Rodney D.
Abstract Mixed neuronal‐glial tumors are rare and challenging to subclassify. One recently recognized variant, papillary glioneuronal tumor (PGNT), is characterized by prominent pseudopapillary structures and glioneuronal elements. We identified a novel translocation, t(9;17)(q31;q24), as the sole karyotypic anomaly in two PGNTs. A fluorescence in situ hybridization (FISH)‐based positional cloning strategy revealed SLC44A1, a member of the choline transporter‐like protein family, and PRKCA, a protein kinase C family member of serine/threonine‐specific protein kinases, as the 9q31 and 17q24 breakpoint candidate genes, respectively. Reverse transcription‐polymerase chain reaction (RT‐PCR) analysis using a forward primer from SLC44A1 exon 5 and a reverse primer from PRKCA exon 10 confirmed the presence of a SLC44A1‐PRKCA fusion product in both tumors. Sequencing of each chimeric transcript uncovered an identical fusion cDNA junction occurring between SLC44A1 exon 15 and PRKCA exon 9. A dual‐color breakpoint‐spanning probe set custom‐designed for interphase cell recognition of the translocation event identified the fusion in a third PGNT. These results suggest that the t(9;17)(q31;q24) with the resultant novel fusion oncogene SLC44A1‐PRKCA is the defining molecular feature of PGNT that may be responsible for its pathogenesis. The FISH and RT‐PCR assays developed in this study can serve as valuable diagnostic adjuncts for this rare disease entity.